Withaferin A Induces Oxidative Stress-Mediated Apoptosis and DNA Damage in Oral Cancer Cells - Chang, Hsueh-Wei; Li, Ruei-Nian; Wang, Hui-Ru; Liu, Jing-Ru; Tang, Jen-Yang; Huang, Hurng-Wern; Chan, Yu-Hsuan; Yen, Ching-Yu (Frontiers in Physiology, 2017)
Withaferin A (WFA) is one of the most active steroidal lactones with reactive oxygen species (ROS) modulating effects against several types of cancer. ROS regulation involves selective killing. However, the anticancer and selective killing effects of WFA against oral cancer cells remain unclear. We evaluated whether the killing ability of WFA is selective, and we explored its mechanism against oral cancer cells. An MTS tetrazolium cell proliferation assay confirmed that WFA selectively killed two oral cancer cells (Ca9-22 and CAL 27) rather than normal oral cells (HGF-1). WFA also induced apoptosis of Ca9-22 cells, which was measured by flow cytometry for subG1 percentage, annexin V expression, and pan-caspase activity, as well as western blotting for caspases 1, 8, and 9 activations. Flow cytometry analysis shows that WFA-treated Ca9-22 oral cancer cells induced G2/M cell cycle arrest, ROS production, mitochondrial membrane depolarization, and phosphorylated histone H2A.X (γH2AX)-based DNA damage. Moreover, pretreating Ca9-22 cells with N-acetylcysteine (NAC) rescued WFA-induced selective killing, apoptosis, G2/M arrest, oxidative stress, and DNA damage. We conclude that WFA induced oxidative stress-mediated selective killing of oral cancer cells.